Pengaruh Latihan Kekuatan dan Latihan Keseimbangan terhadap Kebugaran Fisik, Kesehatan Mental, dan Kesejahteraan Sosial Atlet Para-Judo: Sebuah Studi Eksperimental - Dyah Sukma Ramadhani; Abdul Rahman Syam Tuasikal; Nanik Indahwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the effects of strength and balance training on physical fitness, mental health, and social well-being among male para-judo athletes affiliated with the National Paralympic Committee Indonesia (NPCI). A quantitative research design employing a one-group pretest–posttest model was used. Ten male para-judo athletes (J1 = 6, J2 = 4; age range 20–29 years) participated in an eight-week structured program. Instruments included physical fitness tests (grip strength, bench press, deadlift, sit-up, back-up), balance assessment (standing stroke test blind), and psychological evaluation using the WHO-5 Well-Being Index and social welfare scale. Data were analyzed using paired t-tests with a significance level of p < 0.05. Findings revealed significant improvements across all physical variables (p < 0.01), including grip strength, deadlift, and sit-up performance. Mental well-being scores increased significantly (mean difference = 3.5, p = 0.002), as did social welfare (mean difference = 4.2, p = 0.004). The effect size (Cohen’s d = 0.81) indicated a strong influence of the combined strength and balance training on all three domains. An eight-week integrated strength and balance training program significantly enhanced the physical fitness, mental well-being, and social welfare of visually impaired para-judo athletes. These findings underscore the importance of a holistic and evidence-based training framework for promoting both performance and quality of life among athletes with disabilities. Keywords: Para-judo, strength training, balance training, mental health, social well-being, disabled athletes